Review of Maqasid Syariah on Reto Tuo as A Waqf Member In Bengkulu, Indonesia - Isnaini, Desi (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
This study aims to analyze the implementation of reto tuo as an expert waqf in Bengkulu Province in the maqasid sharia review. This research is a qualitative research that is descriptive analytic because this research describes the application of expert waqf in Bengkulu Province. The data used in this study were obtained directly from interviews conducted with families who carry out ahl waqf, heirs who are managed by expert waqf, as well as community leaders in Bengkulu Province. In this study, the researcher used the maqāṣid asy-syarīah theory of Imam asy-Syȃtibî to see how Islamic law views the practice of Reto tuo as an expert waqf within the framework of maqāṣid asy-syarīah Imam asy-Sytibî, especially on the concept of the objectives of the Shari'a on guarding and protecting against five main elements, namely religion, soul, mind, descent and property. The results showed that the practice of Reto Tuo can be categorized as expert waqf, this is in accordance with the definition of waqf experts that the assets or benefits that are waqf (waqif) to the recipients of waqf (mauquf 'alaih) are waqif descent which is intended for virtue. In this context, it can be seen that the practice of Reto tuo has attempted to maintain the continuity of the assets owned by the family which are managed by their parents, with the hope that the maintenance of these assets can be used by the family when their parents have died. The care of family assets is the key to ensuring the continuity of family life as well as protection of the human soul in the family individually.